2004
DOI: 10.1203/01.pdr.0000132664.66975.79
|View full text |Cite
|
Sign up to set email alerts
|

Differential Maturation of the Innate Immune Response in Human Fetuses

Abstract: Newborns and especially preterm infants show a unique susceptibility to severe bacterial infections that cause significant morbidity and mortality. As very few data are available on innate immune functions in human fetuses, we conducted a comprehensive study to investigate the expression of several adhesion molecules essentially involved in migration (CD11a, CD11b, CD11c, CD18, and CD62L). Furthermore, phagocytic activity, generation of respiratory burst products, and production of several proinflammatory cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
90
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 44 publications
(41 reference statements)
6
90
0
1
Order By: Relevance
“…Phagocytosis and intracellular killing by neonatal monocytes are comparable to those achieved by adult MNCs (25)(26)(27)(28)(29). However, these data are derived from stimulation studies using early-onset sepsis pathogens or latex particles; there are no analogous data on phagocytosis of SE by monocytes in preterm infants.…”
Section: Monocyte Surface Expression Of Tlrsmentioning
confidence: 99%
“…Phagocytosis and intracellular killing by neonatal monocytes are comparable to those achieved by adult MNCs (25)(26)(27)(28)(29). However, these data are derived from stimulation studies using early-onset sepsis pathogens or latex particles; there are no analogous data on phagocytosis of SE by monocytes in preterm infants.…”
Section: Monocyte Surface Expression Of Tlrsmentioning
confidence: 99%
“…There are no definitive comparisons of phagocytosis between adults and neonates; studies have identified positive (12,13), negative (14), and neutral (11,13) trends in functionality between the groups (15). Similarly, the reported correlation between GA and phagocytosis functionality is inconsistent (12,16). Discrepancies are also evident when comparing specific cell types, including monocytes and neutrophils (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…The ability of biofilm-producing bacteria to avoid immune clearance and the general immaturity of the neonatal immune system (12) are postulated to increase the risk of neonatal SE sepsis (13). As compared with adults, neonates have a lower quantitative and qualitative complement activation (14,15), reduced upregulation of cellular response (12), and an immature cytokine response pattern (16)(17)(18)(19). Preterm infants demonstrate a markedly reduced capacity to upregulate oxidative burst in leukocytes in response to SE (20).…”
mentioning
confidence: 99%